What Types of Errors did The Students Make In Using Simple Past In Writing Narrative Text? - Yosafat Tabasi*; Rifaldy Poliwo; Irsan Bertinus Tondowalao; Yuyun Alfasius Tobondo; Masril Aguswandi Tudjuka; Atika Novince (Universitas Syiah Kuala, 2023)
The researcher interesting to analyze the error mistake in narrative text. The researcher will be using error analysis, because it is the process of determining the incidence, nature, causes and consequences of unsuccessful language. Error analysis is very important because the researcher would to the types of errors done by students on using past tense in narrative text. This qualitative research seeks to understand a scientific phenomenon related to the interaction of human behavior in certain situations according to the views and ways of thinking of the researchers themselves. Based on research result could be concluded that there was many errors of using past tense in translating Indonesian narrative text that made by students of Semester V of English Education Study Program, Teacher Training and Education Faculty of Christian University of Tentena It means that past tense sentences need to teach and practice to the student. This research was expected all element could work together to minimize the occurrence of errors by the students in writing paragraphs especially using tenses.